Advances in the synthesis, characterisation, and mechanistic understanding of active sites in Fe-zeolites for redox catalysts. Issue 42 (17th August 2020) - Bols, Max L.; Rhoda, Hannah M.; Snyder, Benjamin E. R.; Solomon, Edward I.; Pierloot, Kristine; Schoonheydt, Robert A.; Sels, Bert F.
Abstract : Strategies for further research and developments on active sites in Fe-zeolites for redox catalysis. Abstract : The recent research developments on the active sites in Fe-zeolites for redox catalysis are discussed. Building on the characterisation of the α-Fe/α-O active sites in the beta and chabazite zeolites, we demonstrate a bottom-up approach to successfully understand and develop Fe-zeolite catalysts. We use the room temperature benzene to phenol reaction as a relevant example. We then suggest how the spectroscopic identification of other monomeric and dimeric iron sites could be tackled. The challenges in the characterisation of active sites and intermediates in NOX selective catalytic reduction catalysts and further development of catalysts for mild partial methane oxidation are briefly discussed.